The Pyramids of Egypt - Iorwerth Eiddon Stephen Edwards 1909-1996. (UK Penguin Books, 1985)
Chronicles the rise and decline of the pyramids as funerary monuments and discusses how they related to ancient Egyptian society, how they were built, and how researchers are studying them to learn more about the Egyptian culture
Mastabas and early burial customs -- Step pyramids -- The transition to the true pyramid -- The Giza group -- Pyramids of the Vth and VIth dynasties -- Middle Kingdom pyramids -- Later pyramids -- Construction and purpose -- Table of the major pyramids of the Old and Middle Kingdoms
Keywords: Pyramids -- Egypt; General; Ancient Egypt; Archaeology